Épandage agricole des biosolides municipaux : contenu en métaux et en PBDE du lait de vache - Marc Hébert (Éditions en environnement VertigO, 2011)
The impact of land application of biosolids (treated municipal sewage sludge) on dairy milk quality was measured in real farm operating conditions where biosolids were applied in accordance with the regulatory framework prescribed in the province of Quebec (Canada).  The milk from 14 farms receiving biosolids were sampled in the Saguenay region in December 2009 and compared to milk from 14 control farms. The tested farms had used biosolids an average of 11 years. Statistical analysis revealed no difference in the content of inorganic contaminants (arsenic, copper, molybdenum, zinc and thallium) in milk. These results suggest absence of induced hypocupriosis for dairy cows from farms using biosolids. However, the content of polybrominated diphenyl ethers (PBDEs) was higher in milk sampled from the farms using biosolids. Differences could be due, in part, by variability of exposition to dust among farm buildings. PBDE levels were however very low (mean value of 7,2 ng/L), and remained 3-7 times lower than the average levels recorded for various dairy products in the United States and Europe (fat content basis). These low levels could be linked, in part, to lower air depositions on forage in the Saguenay region or lower dust contamination in farm buildings. Based on these results, current knowledge and available data, the application of municipal biosolids under Québec regulations would have no significant impact on PBDE exposure for consumers of dairy products produced in Quebec.